Revascularization vs. Conservative Medical Treatment in Patients With Chronic Kidney Disease and Coronary Artery Disease: A Meta-Analysis - Liao, Guang-zhi; Li, Yi-ming; Bai, Lin; Ye, Yu-yang; Peng, Yong (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: As a strong risk factor for coronary artery disease (CAD), chronic kidney disease (CKD) indicates higher mortality in CAD patients. However, the optimal treatment for patients with two coexisting diseases is still not well defined. Methods: To conduct a meta-analysis, PubMed, Embase and the Cochrane database were searched for studies comparing medical treatment (MT) and revascularization (percutaneous coronary intervention [PCI] or coronary artery bypass grafting [CABG]) in adults with CAD and CKD. Long-term all-cause mortality was evaluated, and subgroup analyses were performed. Results: A total of 13 trials met our selection criteria. Long-term (with at least a 1-year follow-up) mortality was significantly lower in the revascularization arm (relative risk [RR] =0.66; 95% confidence interval [CI]= 0.60–0.72) by either PCI (RR=0.61; 95% CI= 0.55-0.68) or CABG (RR=0.62; 95% CI=0.46-0.84). The results were consistent in dialysis patients (RR=0.68; 95% CI=0.59-0.79), stable CAD patients (RR=0.75; 95% CI=0.61-0.92), ACS patients (RR= 0.62; 95% CI=0.58-0.66) and geriatric patients (RR=0.57; 95% CI=0.54-0.61). Conclusions: In CKD patients with CAD, revascularization is more effective in reducing mortality than medical treatment alone. This observed benefit is consistent in stable CAD and elderly patients. However, future RCTs are required to confirm these findings.